Rhinovirus Induces Basolateral Release of IL-17C in Highly Differentiated Airway Epithelial Cells - Jamieson, Kyla C.; Wiehler, Shahina; Michi, Aubrey N.; Proud, David (Frontiers in Cellular and Infection Microbiology, 2020)
Human rhinovirus (HRV) is a major trigger of acute exacerbations of both asthma and chronic obstructive pulmonary disease. The airway epithelium is the primary site of HRV infection, and responds by releasing proinflammatory and antimicrobial cytokines. Epithelial cells release IL-17C in response to exposure to bacterial, viral, and fungal pathogens. We previously demonstrated a role for HRV in IL-17C production from undifferentiated epithelial cells, and showed that IL-17C could play a role in neutrophil recruitment. To extend these observations, highly differentiated human bronchial epithelial cells (HBE) were infected apically with HRV to assess the effect of dose, time, viral replication, and strain on the IL-17C response. Cellular lysates, and basolateral and apical secretions were analyzed for IL-17C and CXCL1 protein release following HRV or IL-17C stimulation. Upon HRV infection, IL-17C protein was exclusively released basolaterally in a dose-, time-, and viral replication-dependent manner. Several strains of rhinovirus were capable of inducing IL-17C release. Enriched columnar epithelial cell populations contained significantly higher viral titer, and expressed significantly more IL-17C mRNA than enriched basal cell populations. In addition, the kinetic profile of IL-17C release following HRV treatment closely mimics viral shedding kinetics, further implicating the role of rhinovirus replication in IL-17C production. Basolateral treatment of HBEs with IL-17C resulted in a dose-dependent increase in basolateral CXCL1 production. In summary, replicating rhinovirus drives basolateral IL-17C protein release from both apical and basal epithelial cells, which may then act in an autocrine/paracrine manner to promote basolateral CXCL1 protein release.